Chip shots. - Webb, C.E.
Electrical engineers are teaming up with gene jockeys and drug developers to invent new drug-delivery systems that marry electronics and semiconductors to biotechnology. Experts agree that new drugs need a degree of intelligence to get where they must go and to arrive on time, and that's where semiconductors come in.
Keywords: BioMEMS; Biotechnology; Drug delivery systems; Drug reservoirs; Implanted microchips; Implanted semiconductor; Medical implants; Pharmaceutical companies; Silicon microchips